SOCIO-DEMOGRAPHIC DETERMINANTS OF SOCIAL STUDIES KNOWLEDGE AMONG STUDENTS OF UPPER BASIC SCHOOLS IN EBONYI STATE - Dr. Louisa Obiageri Unugo (International Journal of Research Science and Management, 2020)
This research work is carried out on socio-demographic determinants of social studies knowledge among students of upper basic schools in Ebonyi State. It is a descriptive survey research. Three research questions and three hypotheses guided the study. The population of this study comprised all 10, 298 Public Upper Basic II Students in the one hundred and eighty nine (189) Public Upper Basic Schools in the three Education Zones of Ebonyi State. The sample of this study was 515 Upper Basic II Students which represents 5% of the entire population in the area of the study. The instrument that was used for this study was entitled Social Studies Achievement Test (SSAT). The test has fifty two (52) multiple choice items with option A-D to obtain information from students. The questionnaire is made up part ‘A’ and part ‘B’, Part A is on the personal data of the respondents. Part B is on Test of Knowledge of Students in Social Studies. The fifty (50) item of instrument Social Studies Achievement Test (SSAT) was also used for data collection. It was validated by three experts, two of the experts were from Arts and Social Science Education Department (Social Studies Option) of the Ebonyi State University, Abakaliki, while one expert from Measurement and Evaluation Unit of Science Education Department The instrument reliability test was carried out using KudaRichardson 20 (K-20) statistics and a reliability coefficient of 0.91 were obtained. The researcher administered the instrument by issuing using Direct Delivery Technique (DDT) with the help of three research assistants, one from each Education Zones in the State. Data Analysis was done using Descriptive and Inferential Statistics. Mean and standard deviation were used to answer the research questions. Hypotheses 1, 3 and 4 were tested using t-test while hypotheses 2 and 5 were tested using Analysis of Variance (ANOVA). All the hypotheses were tested at 0.05 level of significance. Decision Rule: 0- 24 very low, 25 – 49 low, 50 – 74 high, 75 – 100 very high. From the analysis, the following findings were made among others: The knowledge of students in Social Studies is not influence fully or affected by gender. The level of education of the parents influences or affects the knowledge of students in Social Studies. Based on the findings of this study, the researcher made the following recommendation: There should be a process of feed-back initiated for the Secondary schools in Ebonyi State, especially for students, teachers and parents at the Upper Basic level. This feed-back process shall be a medium whereby teachers and parents maintain regular contacts; sharing information concerning their students/wards. Parents should at all-time listen carefully and closely to their wards, not only to verbal communications but to nonverbal communications and to the emotions that may lie beneath what is said.